2017
DOI: 10.1123/jab.2016-0011
|View full text |Cite
|
Sign up to set email alerts
|

Reliability and Validity of Quantitative Video Analysis of Baseball Pitching Motion

Abstract: Video recordings are used to quantitatively analyze pitchers' techniques. However, reliability and validity of such analysis is unknown. The purpose of the study was to investigate the reliability and validity of joint and segment angles identified during a pitching motion using video analysis. Thirty high school baseball pitchers participated. The pitching motion was captured using 2 high-speed video cameras and a motion capture system. Two raters reviewed the videos to digitize the body segments to calculate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(29 citation statements)
references
References 0 publications
1
25
0
3
Order By: Relevance
“…13 Excellent reliability has been established for two-dimensional video analysis of angular measures of lateral trunk lean in high school pitchers at maximum external rotation (ICC 2,k = 0.90; SEM= 3.2°). 15 Statistical analyses were performed using SPSS software (version 22; SPSS Inc., Chicago, IL, USA), with an alpha level set a priori at p ≤ 0.05. A Pearson correlation coefficient was calculated to determine the relationship between trunk lean in the SLS and lateral trunk lean in pitching.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…13 Excellent reliability has been established for two-dimensional video analysis of angular measures of lateral trunk lean in high school pitchers at maximum external rotation (ICC 2,k = 0.90; SEM= 3.2°). 15 Statistical analyses were performed using SPSS software (version 22; SPSS Inc., Chicago, IL, USA), with an alpha level set a priori at p ≤ 0.05. A Pearson correlation coefficient was calculated to determine the relationship between trunk lean in the SLS and lateral trunk lean in pitching.…”
Section: Methodsmentioning
confidence: 99%
“…A sample size of 29 participants was needed to achieve 80% power to determine if a correlation coefficient differs from zero, with an effect size 0.77 15 , and an alpha level of 0.05.…”
Section: Participantsmentioning
confidence: 99%
“…Video analysis is common in elite sports and covers different areas of application. In individual sports, especially acrobatic sports, video analysis is used to compare and improve complex skills [1]. For quantifying biomechanical aspects of such skills, such as score-relevant kinematic variables of vaults in artistic gymnastics, 3D motion capture (3D video analysis) is used.…”
Section: Introductionmentioning
confidence: 99%
“…Two-dimensional video analysis (2D analysis), if sufficiently accurate, could offer a more practical alternative for measuring kinematics during training, especially since advancements in smartphone and tablet technology are continually making high-definition video capture and analysis more convenient. Aside from convenience while capturing motion, 2D video is faster, cheaper, and requires less prior knowledge compared to 3D analysis [1,7]. Nonetheless, although multiple studies showed moderate validity compared to 3D motion capture and high intrarater reliability of 2D analysis when examining joint angles during simple movements, such as single-leg squats and running [1,[5][6][7], the validity and reliability of 2D video analysis for complex skills in acrobatic sports are unclear and must be scientifically assessed before this method can be recommended for gymnastics.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation